Anti Corruption Disclosure dan Good Corporate Governance Era New Normal di Asia Tenggara - Rusli, Yohanes Mardinata (JURNAL ADMINISTRASI KANTOR; Vol 10 No 1 (2022): Jurnal Administrasi Kantor (Juni 2022), 2022)
This study aims to determine and analyze the effect of good corporate governance with and without being moderated by Audit Quality on Anti-Corruption Disclosure. This research is expected to be a breakthrough and new benefits for the community to find out what factors from corporate governance proxies affect Anti-Corruption Practices Disclosure. The research subjects used in this study are publicly listed companies in Southeast Asian countries, including: Indonesia and Malaysia. While the objects in this study are the Annual Report and Financial Statements for the period 2018-2020 which are published on the Stock Exchanges website of the landmark Asian country. The results of this study state that: (i) In Indonesia: Independent Commissioners and Transparency BOC have a significant effect on Anti Corruption Disclosure in Indonesia, but for the Audit Committee it does not have a significant effect on Anti Corruption Disclosure. In addition, the role of Audit Quality as a moderating variable strengthens the relationship between the Independent Commissioners and the Transparency of the BOC on Anti Corruption Disclosure in Indonesia, but Audit Quality does not play a moderating role between the Audit Committee on Anti Corruption Disclosure in Indonesia. (ii) While in Malaysia, the results of this research state that the Independent Commissioners and the Audit Committee have a significant effect on Anti Corruption Disclosure, but for Transparency BOC does not have a significant effect on Anti Corruption Disclosure. In addition, the role of Audit Quality as a moderating variable strengthens the relationship between the Independent Commissioners and the Audit Committee on Anti Corruption Disclosure in Indonesia, but Audit Quality does not play a moderating role between BOC Transparency and Anti Corruption Disclosure. These two countries represent a country that is part of the Southeast Asian region. The limitation of the study is that the research period was conducted only from 2018-2020 and the population is publicly listed companies in Indonesia and Malaysia. Suggestions for further research to add several independent variables related to the anti-corruption disclosure variable and the countries studied in this study should be added, not only Indonesia and Malaysia.   Keywords : Independent Commissioners, Audit Committee, Transparency of BOC, Audit Quality, Anti Corruption Disclosure